Construction of permittivity functions for high-explosives using density functional theory. (1st January 2012) - Finkenstadt, Daniel; Lambrakos, Samuel George; Bernstein, Noam; Jacobs, Verne L.; Huang, Lulu; Massa, Lou; Shabaev, Andrew
We review a framework for the prediction of explosive molecular spectra, namely, for the common explosives found in improvised explosive devices, e.g., β -HMX. Through the use of excitation by incident electromagnetic waves in the THz frequency range, molecular signatures of these explosives may be detected, identified and perhaps neutralised remotely. A central component of this framework is an S-matrix representation of multilayered composite materials. The individual molecules are first simulated using first-principles density functional theory (DFT). An effective electric permittivity function is then constructed, which yields reflectivity and transmissivity functions of frequency and of angle of incident radiation. The input for this component would be a parameterised analytic-function representation of the electric permittivity as a function of frequency, which is provided by another component model of the framework. The permittivity function is constructed by fitting response spectra calculated using DFT, and parameters are adjusted according to additional information available, e.g., from experimentally-measured spectra or theory-based assumptions concerning spectral features. Finally, a prototype simulation is described that considers the response characteristics for THz excitation of typical high explosives.